Bio-refinery Approach for Spent Coffee Grounds Valorization - Teresa M. Mata (2018)
Although normally seen as a problem, current policies and strategic plans concur that if adequately managed, waste can be a source of the most interesting and valuable products, among which metals, oils and fats, lignin, cellulose and hemicelluloses, tannins, antioxidants, caffeine, polyphenols, pigments, flavonoids, through recycling, compound recovery or energy valorization, following the waste hierarchy. Besides contributing to more sustainable and circular economies, those products also have high commercial value when compared to the ones obtained by currently used waste treatment methods. In this paper, it is shown how the bio-refinery framework can be used to obtain high value products from organic waste. With spent coffee grounds as a case study, a sequential process is used to obtain first the most valuable, and then other products, allowing proper valorization of residues and increased sustainability of the whole process. Challenges facing full development and implementation of waste based bio-refineries are highlighted